1997
DOI: 10.1258/0956462971919255
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Epstein-Barr virus DNA and human papillomavirus DNA in acetowhite lesions of the penile skin and the oral mucosa

Abstract: Oral hairy leukoplakia (OHL), thought to be caused by Epstein-Barr virus (EBV), shows similar histological and clinical features to human papillomavirus (HPV)-related acetowhite lesions of the vulva. We thus aimed to investigate the role of both HPV and EBV in men with acetowhite lesions of the penis. HPV but not EBV was significantly associated with penile acetowhite lesions showing koilocytosis compared with normal penile skin (12/20 versus 5/20, P < 0.02). HPV (5/20) and EBV (6/20) was detected in oral muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In sum, reduced numbers of Langerhans cells and increased expression of HLA-DR molecules on the surface of keratinocytes in the OGE of HIV π CMP patients suggest that the oral gingiva in HIV π patients is atypically affected by the inflammation. This may support the contention that the OGE in patients with HIV infection is under an unusual microbial attack (Sandros et al 1996, Odden et al 1994, Reichart et al 1995, Voog et al 1997, Regezi et al 1996, Myint et al 1999).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In sum, reduced numbers of Langerhans cells and increased expression of HLA-DR molecules on the surface of keratinocytes in the OGE of HIV π CMP patients suggest that the oral gingiva in HIV π patients is atypically affected by the inflammation. This may support the contention that the OGE in patients with HIV infection is under an unusual microbial attack (Sandros et al 1996, Odden et al 1994, Reichart et al 1995, Voog et al 1997, Regezi et al 1996, Myint et al 1999).…”
Section: Discussionsupporting
confidence: 68%
“…The significant reduction in numbers of LC in OGE from HIV π patients and the accumulation of increased numbers of gingival plasma cells in the connective tissue subjacent to the OGE (Myint et al 1999) may therefore indicate that a chronic form of inflammation is taking place in the area. This may be caused by pathogens such as bacteria (e.g., P. gingivalis), yeasts (e.g., C. albicans), and viruses (e.g., Epstein-Barr, human papillomavirus, herpes simplex and cytomegalovirus) that colonize and invade the surface of the oral epithelium in HIV π patients (Sandros et al 1996, Odden et al 1994, Reichart et al 1995, Voog et al 1997, Regezi et al 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Anal swabs from STI clinic attendees, with and without HIV, in G×teborg, Sweden (mean age: 35 years) had an overall HPV prevalence of 77% and an HPV-16/18 prevalence of 27% [87]. This was higher than other Swedish studies from STI clinic attendees in G×teborg (mean age: 31 years) [86], Stockholm (mean age: 27 years) [88], and Uppsala (mean age: 25 years) [90], who had overall penile HPV prevalences of 25%, 13%, and 29%, respectively. An earlier study of STI clinic attendees in Stockholm (mean age: 28 years) [89] reported an overall HPV prevalence of 50% and an HPV-16 prevalence of 13% in men without a history of, or contact with, condylomata.…”
Section: High-risk Central and South American Populations In Centralmentioning
confidence: 67%
“…(ii) The oral part of the mucosa might be exposed to additional antigenic challenges in HIV π patients. Pathogenic bacteria such as Porphyromonas gingivalis (Sandros et al 1996), yeasts (Candida albicans, Odden et al 1994) and viruses (Epstein-Barr, human papillomavirus, herpes simplex and cytomegalovirus) (Voog et al 1997, Regezi et al 1996 may colonize the surface of the oral epithelium of HIV π patients, invade the tissue and provide an unusual antigenic stimulus. (iii) The protective function of oral epithelium might be undermined.…”
Section: Discussionmentioning
confidence: 99%